Herpes Simplex Virus Type 1 Clinical Isolates Respond to UL29-Targeted siRNA Swarm Treatment Independent of Their Acyclovir Sensitivity - Kalke K; Lehtinen J; Gnjatovic J; Lund LM; Nyman MC; Paavilainen H; Orpana J; Lasanen T; Frejborg F; Levanova AA; Vuorinen T; Poranen MM; et al. (MDPI, 2022)
Acyclovir is the drug of choice for the treatment of herpes simplex virus (HSV) infections. Acyclovir-resistant HSV strains may emerge, especially during long-term drug use, and subsequently cause difficult-to-treat exacerbations. Previously, we set up a novel treatment approach, based on enzymatically synthesized pools of siRNAs, or siRNA swarms. These swarms can cover kilobases-long target sequences, reducing the likelihood of resistance to treatment. Swarms targeting the UL29 essential gene of HSV-1 have demonstrated high efficacy against HSV-1 in vitro and in vivo. Here, we assessed the antiviral potential of a UL29 siRNA swarm against circulating strains of HSV-1, in comparison with acyclovir. All circulating strains were sensitive to both antivirals, with the half-maximal inhibitory concentrations (IC50) in the range of 350-1911 nM for acyclovir and 0.5-3 nM for the UL29 siRNA swarm. Additionally, we showed that an acyclovir-resistant HSV-1, devoid of thymidine kinase, is highly sensitive to UL29 siRNA treatment (IC50 1.0 nM; I-max 97%). Moreover, the detected minor variations in the RNAi target of the HSV strains had no effect on the potency or efficacy of UL29 siRNA swarm treatment. Our findings support the development of siRNA swarms for the treatment of HSV-1 infections, in order to circumvent any potential acyclovir resistance.